Perancangan User Experience Aplikasi Pesenin berbasis Mobile menggunakan Metode Design Thinking - Rebecca Octaviani; Ratih Kartika Dewi; Riswan Septriayadi Sianturi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Purchasing through food delivery platforms is one of the ways that Indonesian people often buy food and drinks. The author conducted interviews with 5 respondents to explore obstacles when using food delivery platforms. All respondents felt the problem of daily menus that were too monotonous, the difficulty of finding viral food, and the inability to order large quantities of food for another day on the food delivery platform. Therefore, the solution to the problem is to create a user experience of Pesenin Application mobile-based. The Pesenin application is a food ordering application that is expected to make it easier for users to get food using catering or pre-order service systems. The design of this application user experience is designed using the Design Thinking method because this method focuses on potential users and problems and thinks broadly to find good solutions for potential users. The end of this research is usability testing by testing aspects of effectiveness, efficiency, and satisfaction. Testing the effectiveness aspect resulted in a value of 100%. Testing the efficiency aspect resulted in a value of 0.053 goals/second. Testing the satisfaction aspect using the System Usability Scale (SUS) and getting an average SUS score of 86.56. SUS score of Pesenin application gets B for grade scale, excellent for adjective rating, and acceptable for acceptability.